PENGENALAN ALAT MUSIK TRADISIONAL KOLINTANG DI SD XAVERIUS IV PALEMBANG - Pridson Mandiangan (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract Experts and cultural observer indicates that globalization has reduced the awareness and the compassion of the young people including students towards our own culture. They even failed to understand and even considered our national culture is old-fashioned, obsolete, and outdated. Pursuing and conducting our own culture is regarded as an old fashioned attitude, while on the other hand idolizing foreign culture is regarded as an advancement. The author has taught Kolintang for the past forty years, but never experienced teaching lessons in schools, as the interest and awareness of the students for Kolintang music culture is getting lesser as time goes by. Moreover, the absence of Kolintang instrument in government agencies, companies, schools and other institutions in Palembang has been an indicator for the phenomenon stated above. The Implementer Team as collegiate society, want to contribute for the introduction effort of stimulating the interest of students toward their own culture. The problem is lack of awareness and compassion from the students in Palembang, especially into Kolintang musical instrument. Through this community service program, a single unit of Kolintang musical instrument will be produced for the partner, and it can be used as a visualization of traditional music as a lesson, and it also can be collaborated with other modern musical instruments to be played in extracurricular activity at school. Keywords: awareness, traditional music, kolintang, modern music Abstrak Berbagai pihak terutama para ahli dan pemerhati budaya nasional mengindikasikan bahwa globalisasi telah menggerus perhatian, kecintaan dan kepedulian generasi muda termasuk anak-anak sekolah pada budaya bangsa sendiri. Dapat dikatakan sebagai “gagal faham”, dimana budaya nasional kita dianggap sebagai hal yang kuno, usang dan ketinggalan zaman. Mempelajari serta mengaplikasikan kebudayaan sendiri dianggap sebagai suatu sikap kuno dan tidak mengikuti zaman, tetapi menggandrungi budaya asing dipandang sebagai suatu kemajuan dan gaya hidup modern. Pengalaman empiris penulis selama melatih musik kolintang sejak era delapan puluhan, tidak pernah melatih di sekolah-sekolah, serta semakin hilangnya rasa kecintaan dan kepedulian terhadap seni budaya musik kolintang. Juga, semakin berkurangnya keberadaan musik kolintang di instansi pemerintah, perusahaan, sekolahsekolah dan lembaga lain yang ada di Palembang dan sekitarnya, menjadi indikasi fenomena diatas. Tim Pelaksana sebagai masyarakat perguruan tinggi, ingin berkontribusi pada upaya-upaya pengenalan untuk menstimulasi rasa kecintaan anak-anak sekolah khususnya, pada hasil budaya bangsanya sendiri. Permasalahannya adalah kurangnya kepedulian dan kecintaan para siswa-siswi sekolah di kota Palembang, terhadap musik tradisional kolintang. Melalui program pengabdian kepada masyarakat ini, akan dihasilkan satu unit alat musik kolintang untuk mitra, dapat dijadikan visualisasi musik tradisional untuk pembelajaran, juga dapat dikolaborasikan dengan alat musik modern untuk dimainkan dalam kegiatan ekstra kurikuler di sekolah.